Human Rights and Religious Freedom in the Context of National Law in Indonesia - Agus Tohawi; Triyo Ambodo (Universitas Muhammadiyah Palu, 2024)
This paper examines the intricate relationship between human rights and religious freedom within the context of national law in Indonesia. Despite the constitutional guarantees provided by the 1945 Constitution and Law No. 39 of 1999 on Human Rights, which affirm the right to religious freedom as a fundamental human right, significant challenges persist for minority religious groups. The findings indicate that while Indonesia is committed to pluralism and diversity, local regulations and societal norms often undermine these principles, resulting in discrimination and violence against minority faiths such as the Ahmadiyyah and Baha'i communities. The introduction of new legal frameworks, including a revised criminal code that expands blasphemy laws, poses additional threats to religious freedom, raising concerns about the potential for increased repression of minority religions. This study highlights the need for comprehensive legal reforms to align national laws with international human rights standards and promote a culture of tolerance and respect for diversity. Furthermore, it underscores the importance of community engagement and education in fostering interfaith dialogue and understanding among different religious groups. Ultimately, this research contributes to ongoing discussions about the protection of human rights in Indonesia, emphasizing that genuine commitment to pluralism requires not only legal protections but also societal acceptance and respect for all beliefs.